More Cunning Than Folk: An Analysis of Francis Barrett's 'The Magus' as Indicative of a Transitional Period in English Magic - Priddle, Robert (Université d'Ottawa / University of Ottawa, 2013)
This thesis seeks to define how Francis Barrett’s The Magus, Or Celestial Intelligencer is indicative of a transitional period (1800–1830) of English Magic. The intention and transmission of Barrett’s The Magus is linked to the revival of occultism and its use as a textbook for occult philosophy. This thesis provides a historical background preceding this revival. The aim of the thesis is to establish Barrett’s text as a hybrid interpretation of Renaissance magic for a modern audience. It is primarily by this hybridization that a series of feedback loops would begin to create the foundation for modern occultism. This study utilizes a careful study of primary sources, including a systematic examination of The Magus within its intellectual and social contexts.
Keywords: History; Occultism; Francis Barrett; Western Esotericism; Magic; Eighteenth Century; England